18F-FDG and 68Ga-FAPI PET/CT in the Evaluation of Ground-Glass Opacity Nodule. (May 2021) - Chen, Haojun; Pang, Yizhen; Meng, Tinghua; Yu, Xiuyi; Sun, Long
Abstract : Abstract: A 50-year-old woman with a newly detected pulmonary ground-glass opacity (GGO) nodule underwent PET/CT to determine the likelihood of malignancy. This patient was enrolled in the prospective study (NCT04588064) to determine the effectiveness of 18 F-FDG and 68 Ga-FAPI PET/CT for characterization of the GGO nodule. On PET/CT images, minimal 18 F-FDG uptake but intense 68 Ga-FAPI uptake was observed in this GGO nodule. This patient subsequently underwent video-assisted thoracoscopic surgery, and postoperative pathological examination confirmed the diagnosis of invasive adenocarcinoma. This case presented an example where 68 Ga-FAPI PET/CT showed higher tracer uptake than 18 F-FDG in the malignant GGO nodule.